Method of Memorizing the Quran In Early Childhood Period (Case Studies in TKIT Yaa Bunayya and RA Darussalam Yogyakarta) - Hariyanti, Wahyu Eko; Marhumah, Marhumah (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This study aims to determine the method of memorizing the Quran used TKIT Yaa Bunayya and RA Darussalam. This research is a kind of qualitative research with field research method. Data collected with interviews, observations, and documentation studies. The results of this study are the method of memorizing Al Quran that used in TKIT Yaa Bunayya is classical, private and murottal. While the method of memorizing Al Quran applied in RA Darussalam is simai, murajaah and using audio visual media. From this new method obtained results there are some children who are able to memorize the letter exceeds the target in group B (QS Al Insyirah). The target group A recitation is 12 letters in juz 30 (An Naas - Al Ashr), target group B is 21 letters in Juz 30 (An Naas - Al Insyirah). Factors that supported the program to memorize the Quran in TKIT Yaa Bunayya and RA Darussalam are the same, that are the enthusiastic and enthusiastic of students in the memorization, the parents factor that helps the process of memorizing the childrens at home, the teachers who use the method of learning appropriately and innovatively , as well as facilities that are available at school and at home. While the inhibiting factors are the spirit of the students to memorize sometimes down or the condition is less focused, the condition of parents who are too busy so do not have time to repeat the childs memorization at home, and infrastructure facilities are less available.